Exploration in ash-deposition (AD) behavior modification of low-rank coal by manure addition. (1st October 2020) - Li, Fenghai; Zhao, Chaoyue; Guo, Qianqian; Li, Yang; Fan, Hongli; Guo, Mingxi; Wu, Lishun; Huang, Jiejie; Fang, Yitian
Abstract: High-alkali low-rank coal aggravates ash deposition (AD) during conversion. To mitigate AD formation during its gasification, the AD characteristics of Xiaolongtan lignite (XLT) and Yima coal (YM), their variations from chicken or pig manure addition under a reducing atmosphere, and their mechanisms were investigated by using ash fusion temperature tester, self-made AD analyzer, and X-ray diffractometer. The results indicated that the mass fraction of AD (MAD ) of XLT was higher than that of YM because of the XLT with a high Ca, Fe, Na, and K content. At a low temperature (<950 °C), MAD increased with an increasing content of Na, K, and Fe due to their low melting-point eutectic formations; the MAD decreased with an increase in ash fusion temperature at a high temperature. The MAD of the XLT or YM decreased rapidly (1%–10%) and then decreased slowly (10%–15%) with manure ash addition. The XLT MAD decreased 50.32% for 4.93% chicken manure (CM) addition at 1000 °C. High-P and -Ca CM addition caused the formations of high melting-point Ca3 P2 O8 and KCaPO4, which inhibited alkali silicate generation and made the MAD decrease. Manure addition can mitigate AD formation effectively during low-rank coal gasification. Highlights: A way to mitigate low-rank coal ash deposition (AD) by manure addition was provided. Mixed coal AD mass fractions (MAD ) decreased quickly (1%–10%) and then slowly (10%–15%). High-P and -Ca chicken manure addition caused the formations of Ca3 P2 O8 and KCaPO4 . High melting-point phosphate inhibited alkali silicate formation and made the MAD decrease.